'Life is made of courage and coffee' an ethnography of speciality coffee in São Paulo, Brazil - Parrish, S (2021)
This thesis explores the ways in which specialty coffee is consumed in Brazil, the world’s largest coffee-producing nation and a rising consumer power. A central aim of this thesis is to address how the consumption of a globalised and modern good such as specialty coffee is experienced in a culture and context that has historically been exploited for the production of that very good, and that now finds itself unevenly positioned in the global consumer market. Based on twelve months of ethnographic fieldwork with specialty coffee enthusiasts and professionals in the city of São Paulo, this thesis explores how a network of individuals that I call the ‘apaixonados’—those passionate about coffee—engage individual aspirations and passions to navigate the boundaries and frictions between their local coffee consumer culture and what is discursively constructed as a ‘global coffee community.’